Distinct differences in striatal dysmorphology between attention deficit hyperactivity disorder boys with and without a comorbid reading disability. (30th December 2016) - Goradia, Dhruman D.; Vogel, Sherry; Mohl, Brianne; Khatib, Dalal; Zajac-Benitez, Caroline; Rajan, Usha; Robin, Arthur; Rosenberg, David R.; Stanley, Jeffrey A.
Abstract: There is evidence of greater cognitive deficits in attention deficit hyperactivity disorder with a comorbid reading disability (ADHD/+RD) compared to ADHD alone (ADHD/−RD). Additionally, the striatum has been consistently implicated in ADHD. However, the extent of morphological alterations in the striatum of ADHD/+RD is poorly understood, which is the main purpose of this study. Based on structural MRI images, the surface deformation of the caudate and putamen was assessed in 59 boys matching in age and IQ [19 ADHD/−RD, 15 ADHD/+RD and 25 typically developing controls (TDC)]. A vertex based analysis with multiple comparison correction was conducted to compare ADHD/−RD and ADHD/+RD to TDC. Compared to TDC, ADHD/+RD showed multiple bilateral significant clusters of surface compression. In contrast, ADHD/−RD showed fewer significant clusters of surface compression and restricted to the left side. Regarding the putamen, only ADHD/−RD showed significant clusters of surface compression. Results demonstrate for the first time a greater extent of morphological alterations in the caudate of ADHD/+RD than ADHD/−RD compared to TDC, which may suggest greater implicated cortical areas projecting to the caudate that are associated with the greater neuropsychological impairments observed in ADHD/+RD. Highlights: Distinct surface deformation in the caudate of ADHD with comorbid RD compared to ADHD without RD. Structural and morphological alterations in the putamen were observed only in ADHD without RD. This implicates a greater extent of cortical-striatal network alterations in ADHD with comorbid RD.